2020
DOI: 10.1155/2020/9219825
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Conditioning Effects Are Not Additive to Cardioprotection Induced by Direct NLRP3 Inflammasome Inhibition: Role of RISK, NLRP3, and Redox Cascades

Abstract: Inhibition of either P2Y12 receptor or the nucleotide-binding oligomerization domain- (NOD-) like receptor pyrin domain containing 3 (NLRP3) inflammasome provides cardioprotective effects. Here, we investigate whether direct NLRP3 inflammasome inhibition exerts additive effects on myocardial protection induced by the P2Y12 receptor antagonist Ticagrelor. Ticagrelor (150 mg/kg) was orally administered to rats for three consecutive days. Then, isolated hearts underwent an ischemia/reperfusion (30 min ischemia/60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…121 However, another recent study showed that myocardial protection by ticagrelor is mediated through its antiplatelet properties and not an additive effect involving the inhibition of the NLRP3 inflammasome. 122 Understanding the mechanisms by which Cl − efflux controls NLRP3 inflammasome activation may facilitate the discovery of novel agents or drugs suitable for repurposing to increase clinical benefit for patients with one of a variety of NLRP3-related diseases.…”
Section: Spatiotemporal Activation Of the Nlrp3 Inflammasome Complexmentioning
confidence: 99%
“…121 However, another recent study showed that myocardial protection by ticagrelor is mediated through its antiplatelet properties and not an additive effect involving the inhibition of the NLRP3 inflammasome. 122 Understanding the mechanisms by which Cl − efflux controls NLRP3 inflammasome activation may facilitate the discovery of novel agents or drugs suitable for repurposing to increase clinical benefit for patients with one of a variety of NLRP3-related diseases.…”
Section: Spatiotemporal Activation Of the Nlrp3 Inflammasome Complexmentioning
confidence: 99%
“…S1P and adenosine were shown to reach the highest concentrations in rat hearts protected by ticagrelor. Both S1P and adenosine are involved in RISK pathway activation in the heart [140]. Additionally, ticagrelor was able to prevent endothelial cells against apoptosis due to hypoxia stress.…”
Section: Cardioprotective Properties Of Antiplateletmentioning
confidence: 97%
“…e study of isolated rat hearts revealed that ticagrelor conditioning attenuated NLRP3 inflammasome complex formation through platelets. Cardioprotection evoked activation of RISK pathway and limitation of I/R-induced oxidative stress [140].…”
Section: Platelet Nlrp3 As a Prognostic Factor In Patients Withmentioning
confidence: 99%
“…Mastracola et al tested the role of NLPR3 in C57B1 male mice fed with a high fat high fructose diet (HFHF) using an ex vivo I/R model. The authors found that the HFHF diet upregulated NLPR3 protein content, and this elevation downregulated the RISK/HIF-2alpha pathways (51)(52)(53). Furthermore, NLPR3 has also been proposed as a target in the aging myocardium.…”
Section: Inflammasome: Importance Of Nlpr3 In Agingmentioning
confidence: 99%